A STUDY OF INDEX CARD MATCH (ICM) METHOD ON TEACHING DESCRIPTIVE TEXT TO THE STUDENT’S SPEAKING SKILL AT SEVENTH GRADE STUDENT’S OF MTS AS SAIFIYAH SYAFIIYAH - Haslinda Haslinda (The Ellite of Unira, 2020)
The problems of this study were how is the implementation of Index Card Match in teaching descriptive text to the seventh grade students of MTs As saifiyah Syafiiyah and what are the students’ responses to Index Card Match in teaching descriptive text at the seventh graders of MTs As saifiyah Syafiiyah. The purposes of the study are to describe the implementation of Index Card Match in teaching descriptive text and to know the students’ responses to Index Card Match in teaching descriptive text. The research design was used descriptive qualitative. The research was conducted in MTs As Saifiyah Syafiiyah around 34 students. The data collection techniques are observation and questionnaire. The observation was used to describe the implementation of Index Card Match in teaching descriptive text and questionnaire was used to know the students’ responses to Index Card Match in teaching descriptive text. From the result, the Index Card Match made the students are active to try speaking English, although the first meeting more students are shy and fear to speak English. But, the second meeting the students more active, and enthusiasms. The students can speak English with fun, fluency, loudly without shy and fear. Students have been motivated to involve their speaking through Index Card Match. The students get way to apply speaking with their method.